2015
DOI: 10.1115/1.4029691
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Damage Modeling Techniques for Textile Composites: Review and Comparison With Unidirectional Composite Modeling Techniques

Abstract: Composite structural parts have been successfully introduced in high performance industries. Nowadays, also lower performance, high volume production industries are looking for the application of composites in their products. Especially attractive are textile composites (woven, braided, etc.) because of their better drapability and higher resistance to out-of-plane and dynamic loads. Currently, however, extensive mechanical tests are needed to properly design a composite structure. This is a requirement the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 102 publications
0
45
0
Order By: Relevance
“…The residual stiffness degradation of FRP composite subjected to fatigue loading at various R-ratio need to be quantified and the appropriate parameters should be identified from a series of tensile and fatigue tests and for prediction of the residual stiffness for the laminates [9]. The past studies have shown that the fatigue behaviour of composites is highly dependent on the stress ratio R and the frequency of applied cyclic loading [10,11,12,6,13].…”
Section: Introductionmentioning
confidence: 99%
“…The residual stiffness degradation of FRP composite subjected to fatigue loading at various R-ratio need to be quantified and the appropriate parameters should be identified from a series of tensile and fatigue tests and for prediction of the residual stiffness for the laminates [9]. The past studies have shown that the fatigue behaviour of composites is highly dependent on the stress ratio R and the frequency of applied cyclic loading [10,11,12,6,13].…”
Section: Introductionmentioning
confidence: 99%
“…Sevenois et al [28] review existing fatigue damage modeling techniques for composite materials deployed over the last 15 years. In [28], the discussion about existing fatigue models is carried out through model classification in four groups, namely: "fatigue life models", "residual strength models", "residual stiffness models", and "mechanistic models" [28].…”
Section: Effect Of Inflow Conditions On Wt Fatigue Growth and Modelingmentioning
confidence: 99%
“…In [28], the discussion about existing fatigue models is carried out through model classification in four groups, namely: "fatigue life models", "residual strength models", "residual stiffness models", and "mechanistic models" [28]. Judging on [28], fatigue life models are used to predict remaining useful lifetime (RUL) using life cycles, stress, and laminate stiffness relations often achieved through the experiments.…”
Section: Effect Of Inflow Conditions On Wt Fatigue Growth and Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, some of those methods were difficult to extend to textile composites because of their different structures and failure modes. For braided and woven composites, comprehensive literature reviews (Xu, 2011;Sevenois and Van Paepegem, 2015;Wang et al 2015) unveiled that considering appropriate damage mechanisms was the key issue for analysis of textile composites subjected to fatigue. The entire fatigue process can be divided into different stages, and each stage involves distinct damage modes.…”
Section: Modelling Fatigue Behaviour Of Braided Compositesmentioning
confidence: 99%